Krüppel-Like Factors in Vascular Inflammation: Mechanistic Insights and Therapeutic Potential - Sweet, David R.; Fan, Liyan; Hsieh, Paishiun N.; Jain, Mukesh K. (Frontiers in Cardiovascular Medicine, 2018)
The role of inflammation in vascular disease is well recognized, involving dysregulation of both circulating immune cells as well as the cells of the vessel wall itself. Unrestrained vascular inflammation leads to pathological remodeling that eventually contributes to atherothrombotic disease and its associated sequelae (e.g. myocardial/cerebral infarction, embolism, critical limb ischemia). Signaling events during vascular inflammation orchestrate widespread transcriptional programs that affect the functions of vascular and circulating inflammatory cells. The Krüppel-like factors (KLFs) are a family of transcription factors central in regulating vascular biology in states of homeostasis and disease. Given their abundance and diversity of function in cells associated with vascular inflammation, understanding the transcriptional networks regulated by KLFs will further our understanding of the pathogenesis underlying several pervasive health concerns (e.g. atherosclerosis, stroke, etc.) and consequently inform the treatment of cardiovascular disease. Within this review, we will discuss the role of KLFs in coordinating protective and deleterious responses during vascular inflammation, while addressing the potential targeting of these critical transcription factors in future therapies.